Accuracy of Root ZXII, E-PEX and FIND apex locators in teeth with vital pulp: an in vivo study - Cury, Marina Tolomei Sandoval [UNESP]; Vasques, Ana Maria Veiga [UNESP]; Bueno, Carlos Roberto Emerenciano; Machado, Thiago [UNESP]; Trizzi, Juliana Quintino [UNESP]; Santana, Vitor Da Silva [UNESP]; Dezan-júnior, Eloi [UNESP] (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2021)
This research evaluated, in vivo, the accuracy of three electronic apex locators - EALs (Root ZXII, E-PEX and FIND) in teeth with vital pulp submitted to biopulpectomy, preserving the periodontal stump. For this study, 90 single-rooted teeth with extraction indication were selected. After positive pulpal cold sensitivity test, pulp chamber access was performed. The cervical and middle thirds of root canals were instrumented with Reciproc R25, and the K#15 file was used as a standard instrument to determine working length, forming 2 groups: Constriction (insertion of the instrument until the apical constriction limit) and Foramen (insertion of the instrument until the foramen and then repositioning at constriction, without removing the file from the canal). The hand file was stabilized with a light-cured flow resin. After extraction, the samples were analyzed through microCT SkyScan 1272, with CTAN software, which evaluated the proximity between the tip of the file to the apical constriction, providing data for comparative analysis using Kruskal-Wallis and Dunn tests (p<0.05). There was a statistically significant difference in the abilities of the EALs to detect the apical constriction after reaching the foramen with Root ZX II showing higher accuracy (89%). However, there was no difference in the accuracy of the three EALs in detecting the apical constriction without reaching the foramen. Based on the present results, we conclude that EALs may show accurate measures in detecting apical constriction and foramen, even without damaging the periodontal stump in biopulpectomy.
Keywords: Endodontics; Dental Instruments; Odontometry; Tooth Apex